Critical thinking profile of junior high school students in solving function problems as seen in the face of mathematical ability - liloi, olvi; Sutji Rochaminah; Muh Hasbi; Baharuddin (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to describe the critical thinking profile of eighth-grade students of SMP Negeri 19 Palu in solving mathematical problems on the topic of functions. This type of research is descriptive research with a qualitative approach. The research subjects were three people who were selected based on their level of mathematical ability (high, medium, and low). Data collection techniques included written tests and interviews, with data credibility tested using time triangulation. The results showed that: 1) Students with high mathematical ability fulfilled all critical thinking indicators (focus, reason, inference, situation, clarity, and overview). 2) Students with moderate mathematical ability fulfilled five critical thinking indicators (focus, reason, situation, clarity, and overview) but were not accurate in concluding solutions. 3) Students with low mathematical ability only fulfilled three critical thinking indicators (situation, clarity, and overview) and had difficulty in providing reasons and determining appropriate solution strategies.